Oral and cloacal mycobiota of synanthropic Hemidactylus mabouia (Squamata, Gekkonidae) on edge of Atlantic Forest remnant in northeastern Brazil (Research, Society and Development, 2022)
Synanthropic species can, due to their proximity to humans, disperse infectious agents. Among these species, the lizard Hemidactylus mabouia stands out, which has adapted to life inside human homes. As each animal has its microbiota, composed of fungi and bacteria, its coexistence inside homes, in contact with utensils and instruments used in people's daily lives, makes it a potential vector of infectious agents. This work aimed to investigate the oral and cloacal mycobiota of synanthropic Hemidactylus mabouia, and their variations as a function of seasonality and cloacal rostrum length. The study was carried out in the dry and rainy seasons of 2018, in a residential area in the metropolitan region of Recife surrounded by the Atlantic Forest. Oral and cloacal swabs were used to collect the mycobiota. The cloacal cavity showed the highest number of prevalent fungi, especially Penicillium spp. and Aspergillus spp., which presented prevalences above 50%. Mucor spp. and Penicillium spp. had higher prevalence in the rainy season. The mean fungal richness was significantly higher in the cloacal cavity and was not influenced by seasonality. It is of fundamental importance that there are more studies involving the mycobiota of synanthropic H. mabouia to better understand the lizard-fungus-human being relationship and, from that, to better understand how this relationship can affect the human being.